(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2016)
The Lusophone Journal of Economics and Organizational Management (R-LEGO) is an editorial project of the Department of Economics and Management of the Economics and Management School [ECEO], connected to the Research Centre of the Department (CEO - Economics and Organizational Research Centre). It is aimed at students, teachers, researchers and professionals who share interests and scientific concerns.